Physical and Mechanical Properties of Samama Wood Glulam - Tekat D Cahyono; Syarif Ohorella; Fauzi Febrianto; Trisna Priadi; Imam Wahyudi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
In the present research, four types of samama wood (Anthocephallus macrophyllus) glulam of (3 x 6 x 120) cm3 (thickness, width, length) in size were prepared. Two types of glulam were assembled with the same thickness of lamina and two other types were assembled with lamina of different thickness. The result showed that the average moisture content and densities of the glulam were of 12.48% and 0.41, respectively. The MOE, MOR, and shear strength of the glulam were in the average of 6.08 GPa, 33.06 MPa, 30.08 kg cm-2, respectively. The highest MOE and MOR were obtained by the D type glulam. All types of the produced glulam contributed to the increase of MOE and MOR by 31 and 23% of those of its solid wood, respectively.Keywords: glulam, mechanical properties, physical properties, samama wood